2020
DOI: 10.1111/1365-2656.13329
|View full text |Cite
|
Sign up to set email alerts
|

Negative effect of turbidity on prey capture for both visual and non‐visual aquatic predators

Abstract: The outcome of interactions between predators and prey can shape the structure of an entire community, influencing species composition, size structure and spatial distribution (Englund,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 221 publications
(282 reference statements)
3
35
0
Order By: Relevance
“…Such changes in the turbidity and sedimentary organic matter clearly indicate a markedly reduction of physical disturbance on the benthic habitat. Past studies demonstrated that capture rates of predators decreased with an increase in turbidity (Ortega et al, 2020); however, piscivorous fishes tend to consume more prey and possess greater population sizes in low turbidity conditions (De Robertis et al, 2003;Wenger et al, 2013). Our study also concurred with the above findings by showing a negative relationship between the biomass of P. indicus and turbidity, suggesting that P. indicus improved their foraging efficiency under less turbid environment.…”
Section: Discussionsupporting
confidence: 90%
“…Such changes in the turbidity and sedimentary organic matter clearly indicate a markedly reduction of physical disturbance on the benthic habitat. Past studies demonstrated that capture rates of predators decreased with an increase in turbidity (Ortega et al, 2020); however, piscivorous fishes tend to consume more prey and possess greater population sizes in low turbidity conditions (De Robertis et al, 2003;Wenger et al, 2013). Our study also concurred with the above findings by showing a negative relationship between the biomass of P. indicus and turbidity, suggesting that P. indicus improved their foraging efficiency under less turbid environment.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, the trout group (module 2) showed affinity to smaller lakes with greater Secchi depth, which serves as an integrative proxy for multiple terrestrial factors (e.g., sediment loading) and internal productivity (Tilzer, 1988). Smaller lakes with greater water clarity may therefore provide greater open‐water foraging success for salmonids (Ortega et al., 2020). In contrast, the northern group (module 4) was linked to larger lakes with greater influence of shield lithology, in addition to those with reduced water clarity (as encountered in areas overlaying glacial lake beds).…”
Section: Discussionmentioning
confidence: 99%
“…Features of a complex heterogeneous environment and the presence of multidirectional flows form turbulence and turbidity in the water column of riverbed depressions (Mochek et al, 2019). These factors can have a protective effect on non-predatory fish (Figueiredo et al, 2016;Ehlman et al, 2019;Ortega et al, 2020).…”
Section: Discussionmentioning
confidence: 99%